2014
DOI: 10.1039/c4tc00232f
|View full text |Cite
|
Sign up to set email alerts
|

Reduced efficiency roll-off in light-emitting diodes enabled by quantum dot–conducting polymer nanohybrids

Abstract: Hybridization of colloidal quantum-dots and conducting polymers improves the efficiency roll-off of quantum-dot light-emitting diodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 27 publications
1
52
0
Order By: Relevance
“…Nevertheless, CdSe/CdS/ZnSe nanorods have been recently shown to boost both the efficiency and brightness of QD-LEDs with respect to spherical QDs, possibly due to favorable band offset and enhanced light outcoupling 41 , thus making elongated structures promising candidates for high efficiency QD-LEDs. Using deep-red-emitting (650 nm) CdSe/CdS DiRs together with a polyelectrolytic ETL with mobile Br -counter anions, we obtain all-solution-based QD-LEDs with low turn-on voltage (V ON~3 V), high brightness (1200 cd/m 2 ) and EQE of 6,1%, which is over one order of magnitude higher than literature record EQE for QD-LEDs with all-solution-processed organic CTLs 42-44 and exceeds by ~200% the highest EQE of QD-LEDs embedding vacuum evaporated organic interlayers [45][46][47][48] . Importantly, QD-LEDs incorporating polyelectrolytic ETL show no roll-off of the EQE at high current densities, which further emphasizes the great applicative potential of the proposed strategy.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Nevertheless, CdSe/CdS/ZnSe nanorods have been recently shown to boost both the efficiency and brightness of QD-LEDs with respect to spherical QDs, possibly due to favorable band offset and enhanced light outcoupling 41 , thus making elongated structures promising candidates for high efficiency QD-LEDs. Using deep-red-emitting (650 nm) CdSe/CdS DiRs together with a polyelectrolytic ETL with mobile Br -counter anions, we obtain all-solution-based QD-LEDs with low turn-on voltage (V ON~3 V), high brightness (1200 cd/m 2 ) and EQE of 6,1%, which is over one order of magnitude higher than literature record EQE for QD-LEDs with all-solution-processed organic CTLs 42-44 and exceeds by ~200% the highest EQE of QD-LEDs embedding vacuum evaporated organic interlayers [45][46][47][48] . Importantly, QD-LEDs incorporating polyelectrolytic ETL show no roll-off of the EQE at high current densities, which further emphasizes the great applicative potential of the proposed strategy.…”
mentioning
confidence: 81%
“…The black squared refer instead to QDLEDs with thermally evaporated CTLs of small organic molecules (refs. 10,17,18,[45][46][47][69][70][71][72][73][74] ). The coloured dots indicate the EQE values obtained in this work.…”
mentioning
confidence: 99%
“…This approach was successfully applied to spherical, rod‐like, and tetrapod shaped nanoparticles using different side chain conjugated semiconducting block copolymers as ligands. Dynamic light scattering (DLS) in dilute solution revealed that the NCs were individually dispersed and not aggregated …”
Section: Compatibilization Of Nanoparticles and Polymersmentioning
confidence: 99%
“…This reduced efficiency roll‐off could be explained by the suppression of exciton quenching, as well as an improved charge balance within the active layer. This resulted in devices with stable external quantum efficiencies of EQE = 1.38% and a standard deviation of SD(σ) = ± 0.03% (compared to EQE = 1.20% and SD(σ) = ± 0.11% in case of unfunctionalized QDs which showed a drastic efficiency roll‐off at current densities above 50 mA cm −2 ) …”
Section: Compatibilization Of Nanoparticles and Polymersmentioning
confidence: 99%
See 1 more Smart Citation